Expression and its clinical significance of sPD-1 and sPD-L1 in patients with primary nephrotic syndrome - LV Zhi-an; WANG Juan-ni; YANG Yan-yan (Linchuang shenzangbing zazhi)
Objective To investigate expression and its clinical significance of soluble programmed death protein 1(sPD-1) and soluble programmed death ligand 1(sPD-L1) in patients with primary nephrotic syndrome(PNS).Methods A total of 87 PNS patients admitted to our hospital from April 2016 to April 2019 were selected as the case group, and 87 healthy volunteers receiving physical examinations in our hospital in the same period were used as the control group. Comparison of serum sPD-1 and sPD-L1 levels were conducted between the two groups, between different pathological types of PNS patients, and between PNS patients with different outcomes. Pearson correlation analysis was used to determine the correlation of serum sPD-1 and sPD-L1 levels in patients with PNS, and multivariate logistic regression was used to analyze the risk factors of PNS. Results Before treatment, the serum levels of sPD-1 and sPD-L1 in the case group were significantly higher than those in the control group(P<0.05). The levels of serum sPD-1 and sPD-L1 showed significant difference among three pathological types of PNS patients before treatment(P<0.05). The levels of serum sPD-1 and sPD-L1 showed significant difference among three pathological types of PNS patients after treatment(P<0.05). There were significant differences in serum sPD-1 and sPD-L1 levels between the three pathological types of PNS patients before and after treatment(P<0.05). The serum levels of sPD-1 and sPD-L1 in PNS patients with different outcomes were significantly different after treatment(P<0.05). Serum levels of sPD-1 and sPD-L1 were positively correlated in patients with PNS(P<0.05); sPD-1 and sPD-L1 were independent risk factors for PNS(P<0.05).Conclusions sPD-1 and sPD-L1 are highly expressed in the serum of PNS patients, therefore, the detection of the two indices is of vital importance for the treatment and prognosis evaluation.